PENERAPAN HUKUM PIDANA TERHADAP PELAKU TINDAK PIDANA SIBER DI INDONESIA: ANALISIS PUTUSAN PENGADILAN - Siagian, Agus; Alexander, Dony (Penerbit Lafadz Jaya, 2025)
This study aims to analyze how criminal law is applied to perpetrators of cybercrime in Indonesia through a review of several court decisions. With the increasing use of information technology, cybercrime has become a serious challenge in the criminal justice system. This study uses a normative juridical method with a qualitative approach through literature review and content analysis of court decisions. The results show that the types of cybercrime predominantly handled through the courts include online fraud, defamation, hate speech, and the distribution of illegal content. The application of criminal law by judges is carried out by referring to articles in the Criminal Code and the ITE Law, despite inconsistencies in interpretation and technical obstacles in electronic evidence. Judges' considerations in issuing decisions include aspects of legality, justice, and the social impact of the crime. However, there remains a gap between the ideal principles of justice and legal certainty and the reality of practice in the field. This study recommends harmonization of regulations, increasing the capacity of law enforcement officers, and strengthening jurisprudence as steps to improve law enforcement against cybercrime.